Mitral Stenosis: An Updated Review for Nursing Intervention Protocols - Al-Azmi, Naif Saud; Alasmari, Jawaher Hassan; Alotibi, Abdulrahman Jahaz; Albeladi, Ahlam Saleh; Alotaibi , Moodi Gaed; Aldajani, Faisal Mohammed; Almutairi , Hatem Shabbab; Fallatah, Aminah Abdullah Omar; Alresheedi, Ahmed Mutrik Sanat; Alotaibe, Yasser Gaze Abdullah; Alhydal , Lulwah Saad; Motembak, Maryam Ahmad (Journal of Ecohumanism, 2024)
Background: Mitral stenosis (MS) is a valvular heart disease characterized by the narrowing of the mitral valve, primarily caused by rheumatic fever. This condition leads to impaired blood flow from the left atrium to the left ventricle, resulting in symptoms such as dyspnea, fatigue, and palpitations. If untreated, MS can lead to severe complications like pulmonary hypertension, heart failure, and thromboembolic events. Despite advancements in medical and surgical interventions, MS remains a significant health concern, particularly in developing countries where rheumatic fever is prevalent. Aim: This review aims to provide an updated overview of mitral stenosis, focusing on its pathophysiology, clinical manifestations, diagnostic approaches, and treatment options. Additionally, it emphasizes the role of nursing interventions in managing symptoms, preventing complications, and improving patient outcomes. Methods: The review synthesizes current literature on mitral stenosis, including its etiology, risk factors, diagnostic criteria, and management strategies. It highlights the importance of echocardiography for diagnosis and severity classification, as well as the role of medical, surgical, and nursing interventions. Nursing protocols for monitoring, symptom management, patient education, and infection prevention are discussed in detail. Results: Mitral stenosis is a progressive disease that requires timely intervention to prevent complications. Medical management focuses on symptom control, anticoagulation for atrial fibrillation, and prevention of rheumatic fever recurrence. Surgical options, such as percutaneous mitral balloon valvuloplasty (PMBV) and mitral valve replacement, are effective in severe cases. Nursing care plays a critical role in monitoring fluid balance, managing symptoms, educating patients, and preventing infections. Early detection and coordinated care are essential for improving patient outcomes. Conclusion: Mitral stenosis remains a significant cardiovascular condition, particularly in regions with limited access to healthcare. Effective management requires a multidisciplinary approach, including medical therapy, surgical intervention, and comprehensive nursing care. Early diagnosis, patient education, and adherence to treatment protocols are crucial for improving quality of life and reducing complications